Does recreation specialization affect birders' travel intention?. Issue 6 (1st November 2020) - De Salvo, Maria; Cucuzza, Giuseppe; Ientile, Renzo; Signorello, Giovanni
ABSTRACT: Using data from a survey of Italian birdwatchers, we examined whether recreation specialization affects birders' travel intention through a two-dimensional framework based on the "behavior" and "skills, knowledge, and commitment" constructs. The model was estimated through a partial least squares structural equation "spread" model. We implemented a second-stage analysis, using a seemingly unrelated regression (SURE) model to identify which birder characteristics, attitudes, and preferences significantly affected the path scores. The findings demonstrated a significant and positive relationship between recreation specialization and birders' travel intention, and offer evidence that birders' behavior and skills, knowledge, and commitment were statistically significant lower hierarchical order constructs of recreation specialization. The intensity of these connections varied according to the birder's profile, the source of information used to choose the destination site and the reasons behind the choice of site for birdwatching.